ChemInform Abstract: A Metathesis Reaction Route to Obtain Fine Mg2Si Particles. Issue 26 (1st July 2014) - Itahara, H.; Yamada, T.; Oh, S.‐Y.; Asahi, R.; Imagawa, H.; Yamane, H.
Abstract Mg2Si particles with diameters less than 1 μm are prepared by a solid state metathesis reaction of NaSi, MgCl2, and Na (BN crucible, 650 °C, 10 h).